LANGMUIR-BLODGETT FILMS BASED ON SUPERHYDROPHOBIC SOOT - Nazhipkyzy Meruyert,; Alan Dalton, (Academic Scientific Journal of Chemistry, 2020)
In this paper it was produced Langmuir-Blodgett films based on superhydrophobic soot by Nima CD installation (England). Chloroform was used because it has a low boiling point and is not miscible in water. Consequently, the dispersion can be dropped onto the surface of the water in the Langmuir-Schaefer trough. The superhydrophobic soot was obtained at the Institute of Combustion Problems (Almaty, Kazakhstan) by combustion propan-butan mixture by applying an electric filed. To establish complete information about the structure of the soot obtained, studies were conducted by Raman spectroscopy and a transmission electron microscope (TEM). An analysis of the results of Raman spectra shows that two modifications of carbon are present in the obtained samples - amorphous carbon 1350 cm-1 (D - amorphous) and 1590 cm-1, a graphitized carbon phase. As a result, it was found that the produced Langmuir-Blodgett films have a nanostructure, since soot has a nanoscale (20-60 nm), which is confirmed by electron microscopic and Raman studies.